(untitled) (American International Journal of Business and Management Studies, 2022)
Employee retention is vital for every organization, especially in the banking sector, for a nation’s growing economy. Banking institutions are the platform for the economic growth of a country. The main objective of this study is to find out the influencing factors of employee retention and its impact on employee performance in the financial sector of Bangladesh. This research is qualitative and exploratory in nature, where data have been collected from secondary sources like published articles and renowned journals, including Scopus Database, Springer, ABS, Google Scholar, Emerald, and research gate. From extensive literature, it is assumed that career development, training and development, job satisfaction, attractive compensation package, employee voice, and transformational leadership positively impact employee retention, and employee retention has a significant relationship with employee performance. The organisation’s management can make policies and redesign the work on the basis of the factors presented in this paper, which would lead to a happy workforce. This study will be of value to anyone seeking a better understanding of employee retention to improve employee performance and organizational productivity. JEL Classification Codes: M10, M12.